PENGARUH FINANCIAL DISTRESS, FIRM SIZE DAN GROWTH OPPORTUNITY TERHADAP KEPUTUSAN HEDGING PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TEDAFTAR DI BURSA EFEK INDONESIA - Afrida, Afrida (Eko dan Bisnis: Riau Economic and Business Review, 2021)
Hegding is an alternative to risk management to protect the assets owned by the company due to foreign exchange risk. Hedging using derivative instruments is a common method used by companies. This study aims to determine the effect of financial distress, firm size and growth opportunity both partially and simultaneously on the company's decision making to hedge.The population in this study were mining sector companies listed on the Indonesian stock exchange for the period 2016-2019. The sampling technique used in this study was purposive sampling method in order to obtain a sample of 32 companies. The technique in this study used logistic regression analysis with SPSS version 16 software.The results of the study found the financial distress variable regression coefficient with a value of -0.909 and a value (sig = 0,000 <0.05), then the financial distress variable had a negative effect on the hedging decision. The regression coefficient for the firm size variable with a value of 0.421 and a value (sig = 0.002 <0.05), then the firm size variable has a positive effect on hedging decisions. The regression coefficient of the growth opportunity variable with a value of 0.225 and value (sig = 0.148> 0.05), then the growth opportunity variable has no effect on hedging decisions. The chi-square value is 50.923 with a significance of 0.000 <0.05, which means that the financial distress, firm size and growth opportunity variables simultaneously affect hedging decisions in mining sector companies listed on the IDX for the 2016-2019 period.